1986
DOI: 10.1111/j.1365-2990.1986.tb00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Ethanol Exposure on Physical Growth, Sensory Reflex Maturation and Brain Development in the Rat

Abstract: In the offspring of ethanol-treated rats during gestation (25% ethanol in drinking water) decreased litter size, increased postnatal mortality rate, reduced body weight and body size, delayed ear opening, eyelid opening and teeth eruption, retarded air righting reflex acquisition, impaired brain growth, reduced cortical thickness and delayed maturation of layer Vth's pyramidal neurons: reduced basilar dendritic arborization and decreased number of spines in the apical dendrite, were observed when compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 28 publications
(18 reference statements)
2
14
1
Order By: Relevance
“…The results of the present study also showed that growth in the alcohol-intake group did not catch up with the The eye-opening period is a growth index, and eye-opening occurs on average on postnatal day 12 47) . However, previous studies indicated that eye-opening is delayed in rats with FAS 48) .…”
Section: Body Weight Of Neonatal Rats and Eye-opening Periodmentioning
confidence: 80%
See 1 more Smart Citation
“…The results of the present study also showed that growth in the alcohol-intake group did not catch up with the The eye-opening period is a growth index, and eye-opening occurs on average on postnatal day 12 47) . However, previous studies indicated that eye-opening is delayed in rats with FAS 48) .…”
Section: Body Weight Of Neonatal Rats and Eye-opening Periodmentioning
confidence: 80%
“…However, previous studies have indicated a delay in tooth eruption in rats with FAS 48,49) . In the present study, we observed the tooth eruption status of the lower first molar on postnatal day 20.…”
Section: Eruption Of the Lower First Molarmentioning
confidence: 83%
“…These anomalies have also been reported in rodents exposed to alcohol during gestation and/or during the early postnatal period (Lopez-Tejero et al, 1986;Mattson et al, 2001;Tran et al, 2000). The behavioral deficits seen in offspring of mothers that abuse alcohol during pregnancy as well as in rodents exposed to alcohol during gestation and early postnatal periods indicate that the sensorimotor system is particularly susceptible to alcohol during brain development.…”
Section: Introductionmentioning
confidence: 73%
“…It is clear that alcohol exposure during the critical growth spurt period has significant effects on cortical development. The alcohol-induced dysfunctions in cerebral cortex reported during the period of synaptogenesis contribute, in part, to impaired sensory information processing that may underlie delayed sensorimotor development and impaired fine and gross motor control seen in children with FASD (Burd et al, 2003;Connor et al, 2006;Lopez-Tejero et al, 1986;Streissguth et al, 1984).…”
Section: Postnatal Alcohol Exposure and Pmbsf Area And Barrel Patternmentioning
confidence: 99%
See 1 more Smart Citation